2019
DOI: 10.3390/ma12101651
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Galvanized-45 Steel/AZ91D Bimetallic Material by Liquid-Solid Compound Casting

Abstract: A connection between hot-dip galvanized 45 steel and AZ91D was achieved by liquid-solid compound casting to achieve one material with a better mechanical performance and a light weight. The microstructure and properties of galvanized-steel/AZ91D bimetallic materials were investigated in this study. A scanning electron microscopy (SEM), an energy dispersive spectroscopy (EDS), and an X-ray diffraction (XRD) were applied to analyze the microstructure evolution and formation mechanism of the galvanized 45 steel/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, it is difficult to form a metallurgical bonding between Mg and Fe. In recent years, there have been a number of reports on the solid-liquid composite casting of magnesium alloy and steel [11][12][13][14][15]. Sacerdote-Peronnet et al reported the effects of varying the degree of chemical interaction and specimen thickness on the load-displacement curves between mild steel and magnesium base Mg-Al alloy [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is difficult to form a metallurgical bonding between Mg and Fe. In recent years, there have been a number of reports on the solid-liquid composite casting of magnesium alloy and steel [11][12][13][14][15]. Sacerdote-Peronnet et al reported the effects of varying the degree of chemical interaction and specimen thickness on the load-displacement curves between mild steel and magnesium base Mg-Al alloy [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Zinc coating on steel surface will promote the formation of low melting Mg-Zn eutectic, which can improve the weldability of AZ31 and steel [17]. Cheng et al and Jiang et al studied that the microstructure and mechanical properties of interfacial between AZ91D and 45 steel by solid-liquid composite casting with hot-dip galvanized and hot-dip aluminized 45 steel bars at 720 and 780 • C, respectively [12][13][14]. Zhao et al [15] systematically analyzed the microstructure and mechanical properties of the bonding interface of AZ91D/Al-coated 0Cr19Ni9 bimetal materials by using liquid-solid compound casting.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, high-strength and highly wear resistant bimetallic materials have been attracted worldwide attention and demonstrated important application prospects in aerospace, ships, automobiles, and other fields due to their excellent dual performance structure and the comprehensive high-strength and high wear resistance properties [1][2][3][4][5]. The steel-copper bimetallic materials are one of the typical representatives, combining the advantages of both steel (high strength and stiffness) and copper (high wear resistance), and have been used to fabricate military aerospace rotors [6].…”
Section: Introductionmentioning
confidence: 99%
“…The stable joint is obtained through the melting of the filler metal fed near arc burning between the non-consumable tungsten electrode having the appropriately sharpened tip and the base material, or through the melting of the edges of elements being joined. During braze welding, the filler metal usually has the form of a braze or a special braze welding material, which, exposed to the high temperature of arc and that of the heated base material, undergoes melting and, next, forms the joint through diffusion [23][24][25][26][27]. The TIG heat source is characterised by a high arc temperature restricted within the range of 16000°K to 17000 °K and by the conical shape having an approximate angle of 50° [28][29].…”
Section: Introductionmentioning
confidence: 99%